2023
DOI: 10.1002/jso.27288
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing treatment burden during neoadjuvant therapy for patients with gastrointestinal cancer: A mixed methods analysis

Abstract: Introduction: Neoadjuvant therapy (NT) is increasingly used before surgery for patients with gastrointestinal (GI) cancers. Treatment burden is a patient-centered measure defined as the work of being a patient and characterizes the impact of medical treatment on one's functioning and well-being. While treatment burden has previously been studied in chronic diseases and cancer survivorship, the treatment burden of undergoing NT is unknown.Methods: All patients enrolled in a prospective cohort study evaluating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Successful completion of NT requires the expertise and treatment coordination of medical oncologists, surgeons, radiation oncologists, and other care providers [ 11 ]. Consequently, the complexity of cancer care delivery has significantly increased as NT has become more widely adopted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful completion of NT requires the expertise and treatment coordination of medical oncologists, surgeons, radiation oncologists, and other care providers [ 11 ]. Consequently, the complexity of cancer care delivery has significantly increased as NT has become more widely adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Patients must juggle multiple appointments with medical, radiation, and surgical oncologists as well as numerous visits for imaging, laboratory tests, infusions, and referrals to other providers, all while experiencing the side effects of aggressive cancer treatment, side effects of the tumor left in situ , and uncertainty of whether surgical resection will occur in the future. Indeed, patients experience significant treatment burden during NT [ 11 ]. This complexity of care and treatment burden on patients also significantly impacts caregivers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… 19,20 In addition, cancer-specific FACT instruments for hepatobiliary, colorectal, esophageal, gastric, and bladder were administered as appropriate. In addition, validated instruments on treatment burden and care coordination were administered to participants once during the study; the results from these cross-sectional surveys are reported separately 21 . Regarding mood and symptom trackers built into the app, the mood was recorded on a scale of 0 to 4 with 0 representing “poor mood” and 4 representing “good mood,” and symptoms (nausea or vomiting, diarrhea, constipation, no appetite, pain, fatigue, anxiety, trouble sleeping, not able to focus, depression, hopelessness, and frustration) were rated on a yes/no scale.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7] Although recent research has highlighted the significant treatment burden associated with NT, little research has focused on the patients' primary caregivers. [8][9][10] Caregivers serve an important role by providing emotional and physical support to patients throughout cancer treatment. 11 These individuals often take on the role of coordinating healthcare appointments, transporting patients to appointments, helping with activities of daily living (e.g., showering and cooking), and are the main point of contact for the wider support network of family members and friends.…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages of NT include early treatment of micrometastatic disease, enhanced patient selection to ensure appropriate tumor biology before proceeding with surgery, improved likelihood of margin negative resection, especially among patients with borderline resectable and locally advanced tumors, and an opportunity to test the efficacy of the chemotherapy in vivo 4–7 . Although recent research has highlighted the significant treatment burden associated with NT, little research has focused on the patients' primary caregivers 8–10 …”
Section: Introductionmentioning
confidence: 99%